2017
DOI: 10.21010/ajtcam.v14i4.14
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Plants to Protect Plants and Food Against Fungal Pathogens: A Review

Abstract: Background: Plant fungal pathogens play a crucial role in the profitability, quality and quantity of plant production. These phytopathogens are persistent in avoiding plant defences causing diseases and quality losses around the world that amount to billions of US dollars annually. To control the scourge of plant fungal diseases, farmers have used fungicides to manage the damage of plant pathogenic fungi. Drawbacks such as development of resistance and environmental toxicity associated with these chemicals hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(130 citation statements)
references
References 56 publications
0
125
0
5
Order By: Relevance
“…Additionally, it was the second and third largest producer of soybeans and maize, respectively [23]. Fungal phytopathogens affecting agricultural crops lead to a decrease in their quality and production [24]. They act as a threat to crops [25] through various mechanisms of pathogenesis that compromise the immune system of the plants (Table 1) [24].…”
Section: Agricultural Fungicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was the second and third largest producer of soybeans and maize, respectively [23]. Fungal phytopathogens affecting agricultural crops lead to a decrease in their quality and production [24]. They act as a threat to crops [25] through various mechanisms of pathogenesis that compromise the immune system of the plants (Table 1) [24].…”
Section: Agricultural Fungicidesmentioning
confidence: 99%
“…Fungal phytopathogens affecting agricultural crops lead to a decrease in their quality and production [24]. They act as a threat to crops [25] through various mechanisms of pathogenesis that compromise the immune system of the plants (Table 1) [24]. The use of fungicides against fungal plant diseases improves crop yield, quality, and shelf-life [21,26].…”
Section: Agricultural Fungicidesmentioning
confidence: 99%
“…Our findings, thus, suggest that water soluble fractions of petroleum hydrocarbon possess constituents that can also prevent the mycelial growth and development of the test fungal pathogen. Previous study had reported that agents with inhibitory effect against sporulation, mycelia growth and development would be potential candidate for fungicide agent [7,20,21]. Therefore, water-soluble factions of petroleum hydrocarbon could be used to produce effective fungicide against the test crop pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of synthetic fungicides in agricultural practices reduced the negative impact of many plant fungal diseases and increased the overall yield (Shuping et al, 2017), so it can be concluded that they have effectively done their work in controlling fungal disease, over the decades. Unfortunately, using them repeatedly has resulted in development of fungal resistance and disrupted natural biological systems triggering undesirable effects on non-target organisms (Yoon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, using them repeatedly has resulted in development of fungal resistance and disrupted natural biological systems triggering undesirable effects on non-target organisms (Yoon et al, 2013). Since the 1970s, farmers observed the emergence of pathogens resistance against fungicides (Shuping et al, 2017). Therefore, aiming to find novel crop protection solutions, studies regarding the possible exploitation of biomaterials such as natural pesticides were performed ( Yoon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%